Streptozotocin-deoxycorticosterone Acetate-induced Haematotoxicity, Hepatorenal Damage and Oxidative Stress in Diabetic-hypertensive rats: Protective Role of Losartan, Metformin and Glibenclamide Combination Therapy - Emuesiri Goodies Moke; Benneth Ben-Azu; Emuesiri Kohworho Umukoro; Peace Omewomano Onyilo; Paul Chinwuba; Onos Onoriode Emoyan; Kenneth Kelechi Anachuna; Ighodaro Igbe; Eric Kelly I Omogbai (Biology, Medicine, & Natural Product Chemistry, 2026)
Diabetes mellitus and hypertension frequently coexist, exacerbating organ damage. This study investigated the protective effects of combination therapy with losartan (L), metformin (M), and glibenclamide (G) against Streptozotocin-deoxycorticosterone acetate (STZ/DOCA)-induced injuries in a diabetic-hypertensive rat model. Male Wistar rats were divided into five groups: normal control, STZ/DOCA control, and three treatment groups receiving L+M (LM), L+G (LG), or L+M+G (LMG). Hematological, biochemical, oxidative stress, and histopathological analyses were performed after 8 weeks. STZ/DOCA administration induced significant hematotoxicity, hepatorenal dysfunction, and oxidative stress, evidenced by altered blood parameters, elevated liver enzymes (AST, ALT), increased urea, creatinine, and malondialdehyde (MDA), alongside reduced antioxidants (GSH, SOD). Histopathology revealed severe hepatic and renal damage. All treatments provided protection, with the LMG combination showing the most comprehensive amelioration of all measured parameters and the best preservation of liver and kidney architecture. Triple therapy with losartan, metformin, and glibenclamide demonstrated superior synergistic protection against combined diabetic-hypertensive organ damage, highlighting its potential therapeutic promise for this complex comorbidity